1963
DOI: 10.1901/jeab.1963.6-387
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Increment Size and Reinforcer Volume on Progressive Ratio Performance

Abstract: The progressive ratio schedule requires the subject to emit an increasing number of responses for each successive reinforcement. Eventually, the response requirement becomes so large that the subject fails to respond for a period of 15 min and thereby terminates the session. This point is arbitrarily defined as the "breaking point" of the subject's performance. The measure is quantified in terms of the number of responses in the final completed (i.e., reinforced) ratio run of the session. Previous work has sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
221
2
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(235 citation statements)
references
References 6 publications
8
221
2
4
Order By: Relevance
“…In addition to comparing commodities, BPs have been shown to vary systematically as a function of the stimulus qualities of the commodity or magnitude of the commodity. In general, increasing the amount of commodity delivered per reinforcement increases the BP for that commodity (e.g., Dantzer 1976;Hodos 1961;Hodos and Kalman 1963;Sclafani and Ackroff 2003;Reilly 1999), but Brennan et al (2001) reported an inverted-U function with BP increasing and then decreasing at the highest concentration of a sucrose solution. Given the greater BP for highly palatable food (candy) in monkeys and the role that such food plays in the development of obesity (e.g., Blundell and Finlayson 2004) it was of interest to develop procedures for measuring satiation on both palatable and standard food intake.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to comparing commodities, BPs have been shown to vary systematically as a function of the stimulus qualities of the commodity or magnitude of the commodity. In general, increasing the amount of commodity delivered per reinforcement increases the BP for that commodity (e.g., Dantzer 1976;Hodos 1961;Hodos and Kalman 1963;Sclafani and Ackroff 2003;Reilly 1999), but Brennan et al (2001) reported an inverted-U function with BP increasing and then decreasing at the highest concentration of a sucrose solution. Given the greater BP for highly palatable food (candy) in monkeys and the role that such food plays in the development of obesity (e.g., Blundell and Finlayson 2004) it was of interest to develop procedures for measuring satiation on both palatable and standard food intake.…”
Section: Introductionmentioning
confidence: 99%
“…The response schedule requires that an incremental number of operant responses be made for each commodity delivery or reinforcer, i.e., a progressive ratio (PR). Responding was recorded during a long-single session, in which the animals were given ample time to complete the ever-increasing response requirement, with the session ending when no responses had been made for a long period of time, e.g., 15 min (Hodos and Kalman 1963). The value of the completed response requirement prior to the cessation of responding provided the PR breakpoint (BP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addi-tionally, when sucrose pellets were substituted for the grain-based pellets, breakpoints of lesioned rats were differentially increased as compared to controls. As progressive ratio breakpoints are believed to reflect the amount of effort an animal will exert to obtain a reinforcer [22,23,35,53], these results were interpreted as indicating that the lesion had enhanced the incentive motivational properties of the delivered food pellets. Given the well known involvement of the NACC in rewarded behavior (see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In the progressive ratio procedure, the effects of drugs can be evaluated on two measures of reinforcing efficacy: breakpoint and response rate. The breakpoint is defined as the ratio at which the subject stops responding or the highest ratio completed if a timeconstrained session is used (Hodos 1961;Hodos and Kalman 1963), thus, lower breakpoint values can indicate lower reinforcing value for a reward. Performance under PR schedules of food delivery is considered to reflect the efficacy or motivational strength of food because increases in either deprivation level or reinforcer magnitude increase break points (Hodos and Kalman 1963), and effects on motivation can be separated from overall suppression of response rate (see Stafford et al 1998 for review).…”
mentioning
confidence: 99%